1998
DOI: 10.1093/bja/80.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of continuous and intermittent administration of extradural bupivacaine for analgesia after lower abdominal surgery

Abstract: We have compared intermittent bolus and continuous infusion of extradural local anaesthetic for pain relief in a randomized, double-blind study of 48 patients who underwent major abdominal gynaecological surgery. Each patient received 5 ml of 0.375% bupivacaine hourly, either as a bolus over 5 min or as a constant infusion. Patients who received the intermittent administration technique maintained a more extensive sensory block, reported marginally better analgesia and had a lower requirement for rescue medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 15 publications
1
11
1
Order By: Relevance
“…Regression of sensory block over time, need for regular rescue medication and excessive motor block are all well recognized complications of epidural infusions. [1][2][3][4][5] Support for the greater efficacy of bolus injection of local anaesthetics comes from both cadaveric dissection and clinical study. Cryomicrotome sectioning has shown more uniform spread of liquid in the epidural space, through the intervertebral foraminae, and along nerve sheaths when using large volumes of injectate, and a high injection pressure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regression of sensory block over time, need for regular rescue medication and excessive motor block are all well recognized complications of epidural infusions. [1][2][3][4][5] Support for the greater efficacy of bolus injection of local anaesthetics comes from both cadaveric dissection and clinical study. Cryomicrotome sectioning has shown more uniform spread of liquid in the epidural space, through the intervertebral foraminae, and along nerve sheaths when using large volumes of injectate, and a high injection pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Using data from a previous study comparing regular intermittent bolus to continuous infusion for administration of epidural drug, 2 we calculated that a sample size of 40 patients (20 per group) would give the study a power of >0.9 to detect a statistically significant difference in visual analogue pain scores. This calculation was based on mean (SD) visual analogue pain scores at 4 h of 36 (20) mm in the continuous group and 12 (7) mm in the intermittent group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the outcome of an earlier study assessing these two different modes of epidural drug delivery in patients after lower abdominal surgery agreed with the findings of our study. 5 Previous studies have shown that quality of labor analgesia was improved when multi-orificed catheters were used instead of single orifice catheters. 6 A differential flow of local anesthetic from the orifices of a multi-orificed catheter occurs with a continuous infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Institutions where labor epidural analgesia is maintained by manual analgesic boluses (usually undertaken by nursing staff) will inevitably increase their workload, especially if epidural boluses are to be administered regularly. 5,11 The use of an automated regular bolusing device would, in principle, be a welcome improvement. Even when similar doses were used, regular boluses were associated with a longer duration of labor analgesia than continuous epidural infusion of local anesthetic.…”
Section: Discussionmentioning
confidence: 99%